The identity of Clematis diebuensis (Ranunculaceae) described from southern Gansu, China - Huang, Qiao-Lan; Fei, Wen-Qun; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2025)
Based on consultation of literature, survey of herbarium specimens and observations of living plants in the wild, we demonstrate that Clematis diebuensis (Ranunculaceae), described from Têwo county in southern Gansu, China, is not essentially different from C. sibirica in any characters, a most widely distributed Eurasian species which in China occurs in southern Gansu, northern Heilongjiang, Nei Mongol, northern Ningxia, eastern Qinghai, and Xinjiang. We therefore place C. diebuensis in synonymy with C. sibirica herein. Some notes on the taxonomy and nomenclature of C. sibirica are also given.